2014
DOI: 10.1007/s12035-014-8959-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Attenuates Isoflurane-Induced Caspase-3 Activation and Cognitive Impairment

Abstract: Background Anesthetic isoflurane has been reported to induce caspase-3 activation. The underlying mechanism(s) and targeted intervention(s), however, remain largely to be determined. Vitamin C (VitC) inhibits oxidative stress and apoptosis. We therefore employed VitC to further determine the up-stream mechanisms and the down-stream consequences of the isoflurane-induced caspase-3 activation. Methods H4 human neuroglioma cells over expressed human amyloid precursor protein (H4-APP cells) and rat neuroblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 42 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…In cultured H4 human neuroglioma cells, isoflurane was found to induce caspase-3 activation, cause mitochondrial dysfunction, promote ROS accumulation, induce apoptosis, and reduce cell viability. 114116 Strategies to target these isoflurane-induced events have been demonstrated. 115,116 …”
Section: Innate Immunitymentioning
confidence: 99%
“…In cultured H4 human neuroglioma cells, isoflurane was found to induce caspase-3 activation, cause mitochondrial dysfunction, promote ROS accumulation, induce apoptosis, and reduce cell viability. 114116 Strategies to target these isoflurane-induced events have been demonstrated. 115,116 …”
Section: Innate Immunitymentioning
confidence: 99%
“…Previous studies have shown that isoflurane, a commonly used inhalation anesthetic, may induce the neurotoxicity associated with Alzheimer’s disease (AD) neuropathogenesis, including accumulation of β-amyloid protein and phosphorylation of Tau protein [111], and cause neurobehavior deficits [9, 1219]. However, it remains largely unknown whether isoflurane can also cause DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deficiency in lipoic acid causes cognitive deficiency and deterioration in cerebral retention capacity with little effects on sensory-motor motivational capability thus, long-term insufficiency in glutathione linked enzymes lead to structural and functional neuronal dys-connectivity and impairment of cognitive function, also; lipoic acid improves working memory in rats that treated by lipoic acid for two weeks duration via modulation of glutamate NMDA receptors. 18 Vitamin C modulates brain neurotransmitter system mainly glutaminergic,dopaminergic, cholinergic and serotonergic that are linked in memory, learning and cognitive function, moreover ,vitamin C regarded as important cofactor in the synthesis and releasing of noradrenaline and cerebral acetylcholine 19 ,this may explained the cognitive enhancing effects of lipoic acid that augments endogenous cerebral ascorbate level in aged and healthy subjects also , neurobehavioral effect of different herbs was explained depending on their antioxidant properties . 20 Animal model study showed that mice deficient in gene encoding for vitamin C lactone oxidase developed a sever cognitive impairment due to oxidative stress that measured by F4-neuroprostans, also, vitamin C reverses and attenuate scopolamine induced cognitive impairment in rats due to stimulation of central acetylcholineastrase enzyme at median forebrain bundle or through activation of cholinergic neurons, and in spite of vitamin C does not cross blood brain barrier, 21,22 therefore ,oral and intraperitoneal administration of vitamin C will not elevates cerebral ascorbate level ,but lipoic acid elevate brain ascorbate concentration that be able for central arousal effects which improve attention and learning due to modulation of hippocampal and forebrain glutamate concentration.…”
Section: Resultsmentioning
confidence: 99%